EMPATI DI KAMPUNG SAWAH TERHADAP PERKEMBANGAN KAWASAN DI ABAD KE 21 MELALUI PROYEK MUSEUM - Andhika Nicholas; Mieke Choandi (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
The area of Kampung Sawah used to be covered by rice fields, now it has turned into a luxurious residential area for the residents of Bekasi City. This area has long been known for its agricultural products which have the potential to be the main livelihood for the local population. To avoid the potential of the area being forgotten over time, it is necessary to build a building that can save the movement from time to time in the Kampung Sawah area. The building is in the form of a museum which contains the history and development of agriculture in the Kampung Sawah area. It is hoped that the museum project can become a place to store stories of the development and culture of the Kampung Sawah area from time to time, commemorate and introduce agricultural potential and its products and introduce agriculture in Kampung Sawah to the younger generation as a means of village potential and education for the wider community. The agricultural museum is a place to study the agricultural history of Kampung Sawah, from traditional to modern farming tools, farming techniques methods, etc. In the long run, the Kampung Sawah Agricultural Museum project can become an educational tourist spot for local people and also outside the region. Keywords:  agricultural; farmer; museum; Sawah Village Abstrak   Wilayah Kampung Sawah dulu wilayahnya ditutupi oleh sawah-sawah sekarang sudah berubah menjadi pemukiman mewah warga Kota Bekasi. Sejak dulu kawasan ini dikenal dengan hasil pertaniannya yang berpotensi sebagai mata pencaharian utama bagi penduduk setempat. Untuk menghindari potensi kawasan menjadi terlupakan seiring baerjalannya waktu, maka dibutuhkan membangun suatu bangunan yang dapat menyimpan pergerakan dari masa ke masa wilayah Kampung Sawah. Bangunan berupa sebuah museum yang berisi mengenai sejarah dan perkembangan pertanian di wilayah Kampung Sawah. Diharapakan proyek museum dapat menjadi tempat untuk menyimpan cerita perkembangan dan budaya wilayah Kampung Sawah dari masa ke masa, mengenang dan memperkenalkan potensi pertanian dan hasilnya serta mengenalkan pertanian di Kampung Sawah kepada generasi muda sebagai sarana potensi desa dan edukasi bagi masyarakat luas. Museum pertanian menjadi tempat untuk mempelajari sejarah pertanian Kampung Sawah, mulai dari alat pertanian tradisional hingga modern, metode teknik  bercocok tanam, dll. Dalam jangka panjang, proyek Museum Pertanian Kampung Sawah dapat menjadi tempat wisata edukasi bagi masyarakat lokal dan juga luar daerah.